Centro de Servicios Barrios Unidos (2017)
"The Barrios Unidos service center project is part of an urban renewal plan in the city of Bogotá, located on the western side of Caracas Avenue from 72 to 80. The latter seeks to boost urban activity and generate certain areas of activity Taking into account the strategic location of the metro station in the 72, which is part of the future metro line. The project proposes a public building that is an urban reference and encourages the approach of the public management with the inhabitants and the citizen participation, in addition to foment the interaction of the citizens with a closer and participative government".-- Tomado del Formato de Documento de Grado.